2006
DOI: 10.1111/j.1365-2605.2006.00684.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracytoplasmic sperm injection by testicular sperm in patients with aspermia or azoospermia after cancer treatment

Abstract: The aim of this retrospective study was to evaluate the efficiency of testicular biopsy and intracytoplasmic sperm injection (ICSI) in patients with aspermia or non-obstructive azoospermia (NOA) after cancer treatment. From 1996 to 2003, 30 men with a history of cancer, affected by aspermia or NOA and without sperm cryopreserved before cytotoxic treatment underwent testicular sperm extraction (TESE). In these men, clinical, hormonal and histological characteristics were compared; 13 underwent 39 TESE-ICSI cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 20 publications
3
5
0
1
Order By: Relevance
“…In our study, we have shown that half of the men (50.7%) unable to cryopreserve sperm prior to cancer treatment and diagnosed with permanent azoospermia had successful sperm retrieved with TESE and usable for at least one ICSI cycle, a rate similar to the control group. Our data is in line with the results of previous reports (from a total of 258 patients and 283 surgical retrievals, the rate of sperm recovery was 45.9%) [36][37][38][39][40][41][42][43] and also confirm that not all forms of cancer benefit from successful sperm recovery [39].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, we have shown that half of the men (50.7%) unable to cryopreserve sperm prior to cancer treatment and diagnosed with permanent azoospermia had successful sperm retrieved with TESE and usable for at least one ICSI cycle, a rate similar to the control group. Our data is in line with the results of previous reports (from a total of 258 patients and 283 surgical retrievals, the rate of sperm recovery was 45.9%) [36][37][38][39][40][41][42][43] and also confirm that not all forms of cancer benefit from successful sperm recovery [39].…”
Section: Discussionsupporting
confidence: 93%
“…Cumulative live birth rates per couple in NOA cancer survivors did not differ from non-cancer NOA patients (40 vs. 46.5%), despite the significantly older age of the female partners in cancer survivors. However, compared with data in literature (60 deliveries out of 122 couples = 49.2%) [36][37][38][39][40][41][42][43], we showed a lower live birth rate, and this might reflect the mean older age of the female partners in our dataset [44]. The rate of first trimester (< 12 weeks) miscarriage were higher in both NOA and RE/FOE cancer survivors, than in the non-oncologic controls.…”
Section: Discussionsupporting
confidence: 52%
“…These reports of successful pregnancies with cryopreserved sperm in male cancer survivors are supported by numerous other studies [Meseguer et al 2006;Zorn et al 2006;Agarwal et al 2004;Ginsburg et al 2001;Lass et al 1998;Rosenlund et al 1998;Khalifa et al 1992;Palermo et al 1992].…”
Section: Surgical Sperm Retrievalsupporting
confidence: 60%
“…Alkylating agents are the most toxic to Leydig and Sertoli cells leading to decreased testicular volume and increased FSH. [9] In addition, accidents and critical illnesses, along with requests for posthumous reproduction are increasing the need for TESE procedures. [10], [11]The ability to cryopreserve sperm after testicular extraction allows better coordination with oocyte retrieval.While cryopreservation of testicular sperm is equal to fresh, even among some cohorts of men with NOA [12][16], concern regarding limited sperm viability during the freeze-thaw in men with NOA [8] remain prompting some to perform TESE on the day of egg retrieval to avoid sperm loss from the freeze-thaw [17].…”
Section: Introductionmentioning
confidence: 99%